Migratory vasodilatation of cerebral arteries in MELAS episodes: a case report and literature review - Luo, Ying; Chu, Quanhong; Yu, Taochun; Lu, Xiaoqing; Wang, Yanmei; Li, Jie; Wu, Lingfeng; Shen, Yaoyao (Frontiers in Immunology, 2026)
Mitochondrial encephalomyopathy with lactic acidosis and stroke-like episodes (MELAS) is the commonest inherited mitochondrial disorder. Dilation of the major cerebral arteries is seldom mentioned in MELAS because magnetic resonance angiography (MRA) usually shows normal findings. Here, we described a 24-year-old male patient with MELAS who had migratory vasodilatation of cerebral arteries on MRA and positive antibodies against contactin-associated protein-like-2 in serum during stroke-like episodes (SLEs). Moreover, a total of 18 MELAS cases were included in this literature review. MELAS with cerebrovascular dilatation was mainly seen in young adults and the commonest clinical manifestations were visual symptoms, headache, and seizures. Vasodilatation predominantly occurred in the acute phase of SLEs. Dilation of the major cerebral artery mainly happened in the posterior cerebral artery and the middle cerebral artery. The region of increased cerebral blood flow (CBF) always corresponded to the range of vascular supply of the dilated cerebral artery. Multimodal neuroimaging evaluation is very important for the diagnosis of mitochondrial diseases. Migratory vasodilation of cerebral arteries may be a specific imaging sign of MELAS. Dilation of cerebral artery together with increased CBF not only indicates the clinical onset, but also implies an upcoming stroke-like attack.